Peran Management Accounting System Terhadap Pengambilan Keputusan Strategis Dan Kinerja Manajerial Dimoderasi Ketidakpastian Tugas - Efendi, David; Kusuma, Emeralda Ayu; Respatia, Wimba (Unversitas Islam Madura, 2023)
The research aims to prove empirically: (1) the influence of the Management accounting system (MAS) on strategic decision making, and (2) The role of task uncertainty positively moderates or strengthens the influence of the management accounting system (MAS) on strategic decision making. This type of research is quantitative research. The unit of research analysis is the cooperative manager. Data obtained through questionnaire, which 81 out of 101 questionnaires distributed can be analyzed. The data obtained were analyzed by non-response bias testing, descriptive statistics, validity and reliability tests, classical assumption tests and hypothesis testing. Based on the findings of the data analyzed by the SPSS program, the research findings are: (1) the management accounting system (MAS) has no effect on strategic decision making, and (2) task uncertainty weakens the influence of the management accounting system (MAS) on strategic decision making